The metaphor of dark night in John Henry Newman’s works - Lisowska, Natasza (Filozofia Chrześcijańska, 2019)
The metaphor of dark night has been deeply rooted by John Henry Newman in the Bible, as evidenced in his sermons. In addition, it results from the inspiration of works of the Fathers of the Church, including St. Gregory of Nazianzus, whose poetry he valued, as well as it was taken over from Anglican theologians, Lancelot Andrewes, Bishop Winchester and Thomas Sherlock, Bishop of London. Apparently, this metaphor resounded in The Pillar of the Cloud, and other works confi rm the interpretation that the dark night depicts whole life of man as a pilgrim. Faith helps him to lean on God who leads him home. Certain similarities with this metaphor also occur in the poetry of Luis Rosales, a 20th-century Spanish poet. The dark night is also the season that fell after original sin, making the world unfriendly to man; henceforth he is subject to ignorance, sin and death. However, a believer can see some positive signs that night, which indicate the truth that the world is moving to the end of its path.